Performance enhancement of traditional unpeeled longan dryers with design modification - Nakorn Tippayawong (2018)
Several techniques to increase energy efficiency and reduce energy cost in traditional unpeeled longan drying were investigated. Existing dryers were modified into a new dryer arrangement. Performance analysis in terms of energy utilization index, thermal efficiency and energy cost for both traditional and new designs was carried out. The results indicated that the new dryer consumed less energy and had lower fuel cost than the existing traditional dryer. This was largely due to fuel switching from liquefied petroleum gas to firewood and energy recovery via hot air recirculation inside the dryer. The new dryer with improved design and better energy efficiency was demonstrated.